Emotional intelligence and the performance level of fire officers in Magsaysqay-Bansalan-Matanao (MABAMA) Districts - Dumayas, Francis Keith L.; Corillo, Anthony L. (--Davao del Sur: UM Bansalan College, 2010)
The study dealt the relationship between emotional intelligence and performance. More specifically it sought to answer the following objectives: To present emotional intelligence of Fire Officers in MABAMA in terms of (a) Self-Awareness (b) Social Skills. To determine the level of performance of the Fire Officers in MABAMA according to: (a) Style Approach (b) Duties and Responsibilities (c) ethical standard. To ascertain the significant relationship between emotional intelligence and performance of Fire Officers in MABAMA.